Homing and engraftment of intravenously administered equine cord blood-derived multipotent mesenchymal stromal cells to surgically created cutaneous wound in horses: a pilot project - Mund, Suzanne J. K.; Kawamura, Eiko; Awang Junaidi, Awang Hazmi; Campbell, John; Wobeser, Bruce; MacPhee, Daniel J.; Honaramooz, Ali; Barber, Spencer (MDPI, 2020)
Limb wounds on horses are often slow to heal and are prone to developing exuberant granulation tissue (EGT) and close primarily through epithelialization, which results in a cosmetically inferior and non-durable repair. In contrast, wounds on the body heal rapidly and primarily through contraction and rarely develop EGT. Intravenous (IV) multipotent mesenchymal stromal cells (MSCs) are promising. They home and engraft to cutaneous wounds and promote healing in laboratory animals, but this has not been demonstrated in horses. Furthermore, the clinical safety of administering >1.00 × 108 allogeneic MSCs IV to a horse has not been determined. A proof-of-principle pilot project was performed with two horses that were administered 1.02 × 108 fluorescently labeled allogeneic cord blood-derived MSCs (CB-MSCs) following wound creation on the forelimb and thorax. Wounds and contralateral non-wounded skin were sequentially biopsied on days 0, 1, 2, 7, 14, and 33 and evaluated with confocal microscopy to determine presence of homing and engraftment. Results confirmed preferential homing and engraftment to wounds with persistence of CB-MSCs at 33 days following wound creation, without clinically adverse reactions to the infusion. The absence of overt adverse reactions allows further studies to determine effects of IV CB-MSCs on equine wound healing.